Management in vitro of anthrachnosis (Colletotrichum acutatum Simmonds) in avocado through the use of botanical active principles - Barroso-Ake, Alisa Clementina; Ochoa-Fuentes, Yisa María; Cerna Chávez, Ernesto; Tucuch-Pérez, Marco Antonio; Olalde-Portugal, Victor; Robles-Yerena, Leticia (Ecosistemas y Recursos Agropecuarios, 2021)
Anthracnose is the disease caused by the phytopathogenic fungus of the genus Colletotrichum, that decreases quality and yield. The objective of this work was evaluated botanical active principles (PABs) for its control. The pathogen was isolated, the identification was made morphologically, the pathogen identity confirmation was carried out by means of molecular technique (ITS-PCR). Later, in vitro tests were carried out with D-limonene, eucalyptol and β citronellol. Data was analyzed by probit analysis, ANOVA and Tukey test (p ≤ 0.05). The mycelial growth, percentage of sporulation and germination of conidia were measured. The Colletotrichum acutatum was identified. In the in vitro evaluation, β citronellol showed the greatest effectiveness in the different variables, with inhibition intervals of 29 to 89% in mycelial growth, from 61 to 100% in sporulation, and germination from 96 to 100%. Thus, β citronellol represents a botanical alternative in vitro for anthracnose control.